Plant leaf sources presented to the bee Osmia bruneri, their traits, and their likelihood of being pulped for nest construction - James Cane (21419963) (2025)
A categorized, color-coded version of Table 2 in: Cane and Love (2025) Foliar traits, taxonomic preferences, and foraging effort by Osmia bruneri bees acquiring leaf pulp for nest construction (Hymenoptera: Megachilidae). Biological Journal of the Linnean Society